Zenker’s peroral endoscopic myotomy, or flexible or rigid septotomy for Zenker’s diverticulum: a multicenter retrospective comparison - Al Ghamdi, Sarah S.; Farha, Jad; Moran, Robert A.; Pioche, Mathieu; Moll, Frédéric; Yang, Dennis J.; Hernández Mondragón, Oscar V.; Ujiki, Michael; Wong, Harry; Tantau, Alina; Sedarat, Alireza; Fejleh, M. Phillip; Chang, Kenneth; Lee, David P.; Nieto, Jose M.; Andrawes, Sherif; Ginsberg, Gregory G.; Saumoy, Monica; Bapaye, Amol; Dashatwar, Parag; Aghaie Meybodi, Mohamad; Lopez, Ariana C.; Sanaei, Omid; Yousaf, Muhammad N.; Jovani, Manol; Ichkhanian, Yervant; Brewer Gutierrez, Olaya I.; Kumbhari, Vivek; O’Rourke, Ashli K.; Lentsch, Eric J.; Elmunzer, B. Joseph; Khashab, Mouen A. (Endoscopy, 2021)
Background Treatment of Zenker’s diverticulum has evolved from open surgery to endoscopic techniques, including flexible and rigid endoscopic septotomy, and more recently, peroral endoscopic myotomy (Z-POEM). This study compared the effectiveness of flexible and rigid endoscopic septotomy with that of Z-POEM.Methods Consecutive patients who underwent endoscopic septotomy (flexible/rigid) or Z-POEM for Zenker’s diverticulum between 1/2016 and 9/2019 were included. Primary outcomes were clinical success (decrease in Dakkak and Bennett dysphagia score to ≤ 1), clinical failure, and clinical recurrence. Secondary outcomes included technical success and rate/severity of adverse events.Results 245 patients (110 females, mean age 72.63 years, standard deviation [SD] 12.37 years) from 12 centers were included. Z-POEM was the most common management modality (n = 119), followed by flexible (n = 86) and rigid (n = 40) endoscopic septotomy. Clinical success was 92.7 % for Z-POEM, 89.2 % for rigid septotomy, and 86.7 % for flexible septotomy (P = 0.26). Symptoms recurred in 24 patients (15 Z-POEM during a mean follow-up of 282.04 [SD 300.48] days, 6 flexible, 3 rigid [P = 0.47]). Adverse events occurred in 30.0 % rigid septotomy patients, 16.8 % Z-POEM patients, and 2.3 % flexible septotomy patients (P < 0.05).Conclusions There was no difference in outcomes between the three treatment approaches for symptomatic Zenker’s diverticulum. Rigid endoscopic septotomy was associated with the highest rate of complications, while flexible endoscopic septotomy appeared to be the safest. Recurrence following Z-POEM was similar to flexible and rigid endoscopic septotomy. Prospective studies with long-term follow-up are required.